GLOBALISATION, INEQUALITY AND POVERTY IN NIGERIA: ADVOCACY FOR GLOBAL JUSTICE - Bolanle, Ojo Anthonia (Asian Horizons, 2015)
Globalisation is a phenomenon that has gained increasing importance all over the world in the contemporary age. It is a global trend towards development that brings about integration of the world economy and cultures into a global culture, decreasing transportation costs and the dissemination of information and communication technologies; and also bringing about significant rise in gross trade, Foreign Direct Investment (FDI), capital flows and technology transfers. However, in most developing countries, the current wave of globalisation has been accompanied by increasing concern about its impact on inequality and poverty. It is believed that globalisation which is supposed to reduce inequality and poverty increases these. Nigeria is not exceptional in this situation. Nigeria, like most other Sub-Saharan African States, exists with deep-rooted and endemic inequality and poverty. This paper therefore, in the light of Catholic Church Social Teaching, which teaches that all development should lead to rules and values that secure the needs of human community and the desire for social justice, discusses the level of inequality and poverty in Nigeria, and recommends pro-active measures in confronting poverty and empowerment of the poor through investment in human capital in order to enjoy the benefits of globalisation.